Significaciones y prácticas en torno a la imagen del señor del árbol: un análisis intergeneracional en la población de Cuicuno. - Pajuña Toapanta, Estela Elizabeth (2018)
At the present investigation the production of the sense referring to the popular devotion that generates the image of El Señor del Arbol of Cuicuno was analyzed into two groups: young people and elderly people of the place. The objective of this project was to make a comparison, describe and expose the religious meanings and practices around the advocacy and disseminate the results of this study through audiovisual work. The methodology was designed from a qualitative approach, collecting subjective versions of the participants, to know the meanings they build on the religious image that has lasted for centuries in Cuicuno. The applied techniques were the focal groups and observation cards, being able to determine that the invocation generates the same meaning in young people and adults. While in religious practices, there was a dissimilarity in the two analyzed groups, this both in adults who perform practices and acts of faith in honor of the image and in young people that in a certain part has decreased the interest about practicing these liturgical rites. As a result of the present investigation, new research concerns related to communication and culture have been identified, defined in the following lines: acculturation in young people in Cuicuno and its influence on religious practices, family influence in religious worship, meanings and practices in front of the image in devotees, semiotic approaches about the idea of the so-called miracles.